Analisis Fenomena Tindak Pidana Penimbunan Alat Medis di Masa Pandemi COVID-19 Perspektif Hukum Islam - Anggifatul Hana; Nickmetin Erbakan Zen; Regina Masli (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to analyze the phenomenon of hoarding masks and hand sanitizers during the COVID-19 pandemic based on the Law of the Republic of Indonesia Number 7 of 2014 and Presidential Regulation of the Republic of Indonesia Number 71 of 2015. Islam also prohibits the hoarding of all types of goods that people need or that can referred to as